Home video communication: Mediating "closeness" - Kirk, Dave; Sellen, Abigail; Cao, Xiang (Proceedings of CSCW 2010, 2010)
Video-mediated communication (VMC) technologies are becoming rapidly adopted by home users. Little research has previously been conducted into why home users would choose to use VMC or their practices surrounding its use. We present the results of an interview and diary-based study of 17 people about their uses of, and attitudes towards, VMC. We highlight the artful ways in which users appropriate VMC to reconcile a desire for closeness with those with whom they communicate, and we explore the rich ways in which VMC supports different expressions of this desire. We conclude with discussions of how next-generation VMC technologies might be designed to take advantage of this understanding of human values in communicative practice.